Respostas subagudas de parâmetros hemodinâmicos de indivíduos com COVID-Longa submetidos a um teste cardiopulmonar de exercício - Angelotto, Fernanda Rico (Universidade Federal de São Carlos, 2025)
Exercise-induced stress is associated with physiological changes that begin at the onset of exercise and persist for some time after the session. Additionally, hemodynamic parameters can be influenced by inflammatory conditions such as COVID-19, which causes multisystemic symptoms for up to several months after infection. Therefore, this study investigated the hemodynamic response of patients with long COVID (LC) undergoing a cardiopulmonary exercise test (CPET). The project was approved by the Research Ethics Committee (CAAE: 68303823.5.0000.5504) and included 38 participants divided into four subgroups according to sex and LC history (LC-M; LC-F; CON-M; CON-F). The variables cardiac output (CO), augmentation index (AIx), pulse wave velocity (PWV), reflection coefficient, central systolic pressure (CSP), central pulse pressure (CPP), peripheral vascular resistance (PVR), and total vascular resistance (TVR) were collected at baseline; pre-test; 10, 30, 60 minutes and 24 hours after the test. Analysis of variance (ANOVA) was used, and statistically significant results were considered for p<0.05. Analyses were conducted using GraphPad Prism and R software. Differences were found for PWV, CO, AIx, CSP, CPP, PVR, and TVR exclusively between sexes, with no distinction between the CON and LC groups across different time intervals for the variables (p < 0.05), and all variables returned to pre-test levels within 24 hours. Thus, the findings suggest that the LC condition did not influence hemodynamic parameters, and the observed differences may be attributed to physiological variations between sexes.
Subacute responses of hemodynamic parameters in individuals with long COVID undergoing a cardiopulmonary exercise test
Keywords: Resposta hemodinâmica; COVID-longa; Velocidade da onda de pulso (VOP); Pressão sistólica central; CIENCIAS BIOLOGICAS::FISIOLOGIA::FISIOLOGIA DE ORGAOS E SISTEMAS::FISIOLOGIA CARDIOVASCULAR